Aseptic cavernous sinus thrombosis after internal carotid arterial occlusion in polycythaemia vera. Issue 4 (April 1976) - Melamed, E; Rachmilewitz, E A; Reches, A; Lavy, S
Abstract : Two patients with untreated polycythaemia vera developed intracranial internal carotid arterial occlusion followed by monocular blindness and the characteristic features of ipsilateral cavernous sinus thrombosis. Primary septic source and signs of systemic infection were absent. It is suggested that the predisposing factors in this unusual syndrome were hyperviscosity and venous sludging induced by the basic haematological disorder and progression of the thrombotic process within the internal carotid artery towards its intracavernous portion with occlusion of the ophthalmic artery and of the arterial branches which supply the walls of the sinus.